Based on clinical Ki-67 expression and serum infiltrating lymphocytes related nomogram for predicting the diagnosis of glioma-grading - Zhang, Zhi; Gu, Weiguo; Hu, Mingbin; Zhang, Guohua; Yu, Feng; Xu, Jinbiao; Deng, Jianxiong; Xu, Linlin; Mei, Jinhong; Wang, Chunliang; Qiu, Feng (Frontiers in Oncology, 2022)
Background: Compelling evidence indicates that elevated peripheral serum lymphocytes are associated with a favorable prognosis in a variety of cancers. However, the association between serum lymphocytes and glioma is contradictory. In this study, a nomogram was established to predict the risk of low-grade glioma (LGG, WHO grades I-II) developing into secondary glioma (high-grade glioma, HGG, WHO grades III-IV) through Ki67 expression and serum lymphocytes. Methods: We performed a retrospective analysis of 239 patients diagnosed with LGG and 178 patients with HGG. Immunohistochemistry was used to determine Ki67 expression. Following multivariate logistic regression analysis, a nomogram was established and used to identify the most significant predictive risk factors associated with HGG. The consistency index (C-index), decision curve analysis (DCA), and a calibration curve were used to validate the model. Results: The number of LGG patients with more IDH1/2 mutations and 1p19q co-deletion was greater than that of HGG patients. The multivariate logistic analysis identified Ki67 expression, serum lymphocytes count, and serum albumin (ALU) as independent risk factors associated with HGG, and these factors were included in a nomogram in the training cohort. In the validation cohort, the nomogram demonstrated good calibration and high consistency (C-index=0.794). The Spearman correlation analysis revealed a significant association between HGG and serum lymphocytes count (r=-0.238, P<0.001), ALU (r=-0.232, P<0.001), and Ki67 expression (r=0.457, P<0.001). Furthermore, Ki67 expression was negatively correlated with serum lymphocytes count (r = -0.244, P<0.05). LGG patients had lower Ki67 expression and higher serum lymphocytes compared to HGG patients, and a combination of these two variables was significantly higher in HGG patients. Conclusion: The constructed nomogram is capable of predicting LGG patients at risk of developing HGG. Higher levels of serum lymphocyte count and decreased Ki67 expression imply a lower risk of developing HGG. A decrease in the level of serum lymphocytes and increased Ki67 expression in HGG patients indicate that the tumor is more aggressive.